(untitled) (Journal of Bangladesh Institute of Planners, 2011)
ln consideration of the size of the country, road network and vehicle population, the number of road accidents and deaths and injuries caused by such accidents in Bangladesh are one of the highest in the world. In the recent days, one of the most-talked topics is what can be done to make the road a safe place where death will not be an everyday occurrence. The alarming rate of dreadful road traffic accidents may have increased due to certain reasons: lack of political concern, lack of accountability of the relevant ministers and governmental bodies, incompetent drivers, inadequate punishment etc. In this paper, the road safety situation and some contemporary issues and priorities are briefly discussed in addressing the road safety problem. Fatality in road accidents is a critical phenomenon in developing countries. About 86 percent accident occurs in developing countries, although these countries own only 30 percent of vehicle fleet (Jahan, 2006:120). Providing safer roads through reducing accidents is now a priority issue for policy makers at the national level in developing countries. Using the secondary literature, this paper is intended to focus on the involvement of heavy vehicles and their operators in road accidents as well as their behavioral habits and attitudes. This article also focuses on accident statistics, major causes and finally some recommendations have been provided. Journal of Bangladesh Institute of Planners Vol. 4. Dec 2011, pp. 45 - 55